Podcast Trends as an Alternative Medium of Independent Journalism: a Study of Audience Perceptions of the Redibility and Objectivity of Information - Zulfiah Larisu; Abdul Malik (PT. Anagata Sembagi Education, 2025)
Independent journalism podcasts are now seen as a highly credible source of information, often even more trusted than mainstream media. This is due to the transparency of the narratives presented, consistency in topic selection, and freedom from pressure from certain parties, which allows for the delivery of broader and more diverse perspectives. Audiences rate independent podcasts as relatively objective, although the personal opinions of the podcasters remain influenced. A presentation style that combines conversational formats and storytelling techniques creates emotional intimacy, strengthens trust, and builds listener loyalty. Topics that are current and relevant, presented in a relaxed yet informative manner, are a unique attraction that distinguishes podcasts from conventional media. However, challenges remain, particularly in verifying information and the potential for personal bias, which can affect the accuracy and objectivity of the content. Therefore, audience media literacy is crucial so they can critically review the information they receive. With all their advantages, independent podcasts have the potential to enrich the media ecosystem by providing a more diverse alternative source of information, provided they maintain ethical standards, openness of sources, and transparency in every aspect of their production process.